Micro- and Macroelemental Composition and Safety Evaluation of the Nutraceutical Moringa oleifera Leaves - I. J. Asiedu-Gyekye; S. Frimpong-Manso; C. Awortwe; D. A. Antwi; A. K. Nyarko (Journal of Toxicology)
Moringa oleifera is a multipurpose plant used in Ghana and most parts of Africa. Its high mineral, protein, and vitamins content has enabled its use as a nutraceutical and panacea for various diseases. This study aimed at measuring the micro- and macroelements content of dried Moringa oleifera leaves using energy dispersive X-ray fluorescence spectroscopic (EDXRF) and assessing its toxicological effect in rats. Acute toxicity (5000 mg/kg) and a subacute toxicity studies of the leaf (40 mg/kg to 1000 mg/kg) extract were conducted in rats. Blood samples were assessed for biochemical and haematological parameters. Results showed significant levels of thirty-five (35) elements (14 macroelements and 21 microelements) in M. oleifera extract. There were no observed overt adverse reactions in the acute and subacute studies. Although there were observed elevations in liver enzymes ALT and ALP (P<0.001) and lower creatinine levels in the extract treated groups, no adverse histopathological findings were found. Moringa oleifera dried leaf extract may, therefore, be reasonably safe for consumption. However, the consumption of Moringa oleifera leaves should not exceed a maximum of 70 grams per day to prevent cumulative toxicity of these essential elements over long periods.